2021
DOI: 10.3389/fneur.2021.655800
|View full text |Cite|
|
Sign up to set email alerts
|

New Prediction Models of Functional Outcome in Acute Intracerebral Hemorrhage: The dICH Score and uICH Score

Abstract: Objectives: The original intracerebral hemorrhage (oICH) score is the severity score most commonly used in clinical intracerebral hemorrhage (ICH) research but may be influenced by hematoma expansion or intraventricular hemorrhage (IVH) growth in acute ICH. Here, we aimed to develop new clinical scores to improve the prediction of functional outcomes in patients with ICH.Methods: Patients admitted to the First Affiliated Hospital of Chongqing Medical University with primary ICH were prospectively enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They indicated that the score system had reliable accuracy in predicting HE, and NCCT imaging markers may serve as the key for HE prediction. Yang et al ( 94 ) put forward a new prediction models of functional outcome in acute ICH patients, named ultra-early ICH score, containing admission GCS score (3–4: 2 points; 5–12: 1point), baseline ICH volume ˃ 30 ml (1 point), positive IVH (1 point), infratentorial hemorrhage (1 point), age ≥ 80 (1 point), positive BS (1 point), positive BHS (1 point), and positive IS (1 point). Their results showed that the ultra-early ICH score was a useful clinical assessment tool for risk stratification concerning functional outcomes and provided guidance in clinical decision-making in acute ICH.…”
Section: Application Of Imaging Markers and Suggestions For Cliniciansmentioning
confidence: 99%
“…They indicated that the score system had reliable accuracy in predicting HE, and NCCT imaging markers may serve as the key for HE prediction. Yang et al ( 94 ) put forward a new prediction models of functional outcome in acute ICH patients, named ultra-early ICH score, containing admission GCS score (3–4: 2 points; 5–12: 1point), baseline ICH volume ˃ 30 ml (1 point), positive IVH (1 point), infratentorial hemorrhage (1 point), age ≥ 80 (1 point), positive BS (1 point), positive BHS (1 point), and positive IS (1 point). Their results showed that the ultra-early ICH score was a useful clinical assessment tool for risk stratification concerning functional outcomes and provided guidance in clinical decision-making in acute ICH.…”
Section: Application Of Imaging Markers and Suggestions For Cliniciansmentioning
confidence: 99%
“…Patients with ICH exhibit greater improvement in the subacute phase up to 3 months postincident compared with patients who had ischemic stroke, indicating the importance of training and identi cation of the high-risk population (2). Several predictive models for ICH mortality and functional outcomes have been developed and widely used since 2001 (3)(4)(5)(6)(7)(8)(9)(10)(11). These tools are potentially useful for determining prognosis, selecting patients for potential interventions, and developing individualized treatment strategies (12).…”
Section: Introductionmentioning
confidence: 99%